Metaphilosophy: Ontological and Deontic Forms of Reflection. / Metafilosofía: formas deónticas y ontológicas de reflexión. - SERGEEVICH SAFONOV, ALEXANDER (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article explores the ontological premises of philosophizing. The author proves that these bases are key in the formation of a specific type of ontological reflection. The dominance of ontological reflection in the history of western philosophical tradition allowed many private sciences to take shape inside philosophy. The author shows that private sciences, separating from philosophy, alienate ontological reflection from it, which is the cause of the crisis state of modern philosophy and the exacerbation of problems of a metaphilosophical nature. The author formulates original concepts of ontological and deontic reflection, based on the ideas of Parmenides and Socrates. RESUMEN El artículo explora las premisas ontológicas del filosofar. El autor prueba que estas bases son clave en la formación de un tipo específico de reflexión ontológica. El predominio de la reflexión ontológica en la historia de la tradición filosófica occidental permitió que muchas ciencias privadas tomaran forma dentro de la filosofía. El autor muestra que las ciencias privadas, separándose de la filosofía, enajenan de ella la reflexión ontológica, que es la causa del estado de crisis de la filosofía moderna y la exacerbación de problemas de carácter metafilosófico. El autor formula conceptos originales de reflexión ontológica y deóntica, basados en las ideas de Parménides y Sócrates.